Optimalisasi Politik Pendidikan Nasional melalui Manajemen Berbasis Sekolah - Irjus Indrawan (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2018)
Centrally system of education which implemented by the government does not address the needs of the community and students and hinders the occurrence of democracy in the implementation of education, this is because the centralized system forces and applies uniform policies nationally, therefor the target of the central education policy does not reach the target and not as expected because each region has different diversity, interests and potential of human resources and natural resources. In the current education policy, the autonomy of education is one of the positive policies, because it does not stop in districts and cities, but this policy is directly to schools as the spearhead of the implementation of education. One policy system that is considered good at the school level is what is known as the School Based Management Model (SBM). SBM is one model of education management based on school autonomy or independence in determining the direction, policy and course of education. In the process of implementing SBM education, the community must be included, because the community is the first and foremost layer of the education process. This means that the process of education, quality of education, facilities, and goals of education are also the responsibility of the community.